2021
DOI: 10.1073/pnas.2012666118
|View full text |Cite
|
Sign up to set email alerts
|

“Soft” oxidative coupling of methane to ethylene: Mechanistic insights from combined experiment and theory

Abstract: The oxidative coupling of methane to ethylene using gaseous disulfur (2CH4 + S2 → C2H4 + 2H2S) as an oxidant (SOCM) proceeds with promising selectivity. Here, we report detailed experimental and theoretical studies that examine the mechanism for the conversion of CH4 to C2H4 over an Fe3O4-derived FeS2 catalyst achieving a promising ethylene selectivity of 33%. We compare and contrast these results with those for the highly exothermic oxidative coupling of methane (OCM) using O2 (2CH4 + O2 → C2H4 + 2H2O). SOCM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…One possible explanation for this effect, proposed in previous work on S 2 as an oxidant, is the favorable reaction thermodynamics (Table ). Due to the weaker nature of C–S bonds compared to C–O bonds, the thermodynamic driving force toward total oxidation is far less severe for the S 2 than the O 2 system. Nevertheless, it is also plausible that additional effects such as kinetics play a role in SODHP versus ODHP chemistries since kinetics play an important role in traditional ODHP product distributions . This will be discussed further in the DFT analysis below.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation for this effect, proposed in previous work on S 2 as an oxidant, is the favorable reaction thermodynamics (Table ). Due to the weaker nature of C–S bonds compared to C–O bonds, the thermodynamic driving force toward total oxidation is far less severe for the S 2 than the O 2 system. Nevertheless, it is also plausible that additional effects such as kinetics play a role in SODHP versus ODHP chemistries since kinetics play an important role in traditional ODHP product distributions . This will be discussed further in the DFT analysis below.…”
Section: Resultsmentioning
confidence: 99%
“…Sulfur-containing gases represent another class of alternative oxidants. Previously, this laboratory showed that sulfur vapor, S 2 , can be utilized as an oxidant for various light alkane partial oxidations, including methane coupling, ethane ODH, and ODHP. , Unlike CO 2 –ODHP, SODHP remains exergonic at 500 °C. Furthermore, as shown in Table , the thermodynamic driving force toward total oxidation is also significantly reduced with S 2 compared to O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…reported gaseous S 2 as an alternative oxidant to O 2 for the OCM into ethylene over Fe 3 O 4 -derived FeS 2 catalyst. The authors obtained a 33% selectivity toward ethylene at around 10% conversion of CH 4 . Electrocatalysis has also shown promise, where a mixed metal oxide electrocatalyst grown in situ on the electrode surface promoted OCM into ethylene.…”
Section: Ethylenementioning
confidence: 99%
“…The authors obtained a 33% selectivity toward ethylene at around 10% conversion of CH 4 . 78 Electrocatalysis has also shown promise, where a mixed metal oxide electrocatalyst grown in situ on the electrode surface promoted OCM into ethylene. A 12.1% yield to ethylene was obtained at 41% conversion of CH 4 .…”
Section: Ethylenementioning
confidence: 99%
“…The development of a catalytic process that can directly convert CH 4 into useful chemical feedstocks such as CH 3 OH and C2-C4 hydrocarbons has extensively been pursued. [1][2][3][4][5][6] Among various types of heterogeneous catalysts, Cu-containing zeolites have extensively been investigated as a catalyst for the methane to methanol (MTM) reaction; small pore-zeolites such as CHA, AEI, and AFX frameworks exhibit a better CH 4 reactivity and CH 3 OH selectivity than medium-(MFI) and large-(*BEA and MOR) ones. [7][8][9][10][11] Regarding the active Cu species, the density functional theory (DFT) studies by Yoshizawa and co-workers have confirmed that the activation energy required for the cleavage of the C-H bond of CH 4 , which is the rate-limiting step, is governed by the Cu-O-Cu angle and also depends on the crystallographic position in the zeolite cavity.…”
mentioning
confidence: 99%